2013
DOI: 10.1080/15332667.2013.794103
|View full text |Cite
|
Sign up to set email alerts
|

When Relationship Marketing Goes Wrong: Opportunism and Consumer Well-Being in Consumer-Bank Relationships

Abstract: This article revisits debates surrounding the ethics of relationship marketing in the context of bank-consumer relationships in Egypt.The argument develops the conceptual lens of opportunism, observing that an insight into opportunistic behaviour can help to understand why, when implemented, relationship marketing may often play out in unintended (and often unethical) ways. The article describes an interpretive analysis of 25 interviews with Egyptian bank consumers. Two overlapping sets of opportunistic behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Consumers were aware of this fact and mentioned this in their posts by using "target" and "incentive" words in the deception clusters, referring to the sales targets and sales incentives of the salespeople. The sales staff confronts a dilemma between these targets and consumer well-being, and some consumers perceive that they are deceived when there is an over-focus on sales (Elsharnouby and Parsons, 2013;Friend et al, 2020).…”
Section: Discussion and Managerial Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consumers were aware of this fact and mentioned this in their posts by using "target" and "incentive" words in the deception clusters, referring to the sales targets and sales incentives of the salespeople. The sales staff confronts a dilemma between these targets and consumer well-being, and some consumers perceive that they are deceived when there is an over-focus on sales (Elsharnouby and Parsons, 2013;Friend et al, 2020).…”
Section: Discussion and Managerial Implicationsmentioning
confidence: 99%
“…Customer trust and relationship management are very relevant in banking services since the perceived risk is high (Guenzi and Georges, 2010). Ethics and customer relationship management accompany each other, and relationships in the banking sector are quite distinct since they should be based on a high level of trust and are mainly regulated by strict laws (Elsharnouby and Parsons, 2013). In the financial services sector, the ethical sales behavior of frontline employees positively influences customer satisfaction, trust and loyalty (Roman, 2003;Tolba et al, 2015).…”
Section: The Theoretical Background 21 Unethical Sales Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other informants recounted additional examples of perceived vulnerability, such as giving priority in healthcare service appointment booking to those who are the same nationality of the receptionist and selling products at higher prices to locals in mall kiosks and small stores or providing higher hotel rates for locals booking a room than expatriates booking a room. Fundamentally, consumer categorization represents one of the key controversial issues in marketing literature and practice (Elsharnouby & Parsons, 2013; Kavali et al, 1999). The irony here is that the consumer acculturation literature has addressed consumer vulnerability or marginalization in situations where brands target the ethnicity of the majority and ignore minorities, who are usually immigrants (e.g., Kipnis et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Grayson and Ambler (1999) showed that longer-term relationships have negative consequences such as rising expectations, a loss of objectivity and opportunism, which may negate the positive consequences of a relationship. The dark-side of relationship has been studied and explained in different ways, and some solutions have been explored to overcome these negative consequences (e.g., Anderson and Jap, 2005;Elsharnouby and Parsons, 2013;Fang et al, 2011;Villena et al, 2011). The negative consequences of relationship have also been investigated in construction and project contexts; for instance, Jin and Ling (2005) showed that an increasingly close relationship may lead to self-interest seeking actions and opportunistic behaviour.…”
Section: Relationship Marketing In Project-based Firmsmentioning
confidence: 99%